Covid-19 Vaccination in Malang City as an Implementation of Religious Moderation from the Perspective of Islamic Law - Miftahudin Azmi (NUR EL-ISLAM : Jurnal Pendidikan dan Sosial Keagamaan, 2021)
The polemic about Covid-19 pandemic is indeed quite complicated, especially when it is accompanied by the rise of hoax news on various social media pages. The vaccination program promoted by the government initially encountered problems, some religious leaders refused to implement the vaccine because the raw material used came from pig trypsin. This condition makes it difficult for the government to cope with the COVID-19 pandemic. This study uses an empirical juridical approach by knowing the response of the people of the city of Malang in responding to the Covid-19 vaccination and analyzed with a maqashid sharia approach. The results showed that at first the people of Malang City were not enthusiastic about implementing the vaccine because it was influenced by information that developed on social media. However, in the end they were willing to be vaccinated after knowing the truth of the news and the importance of the covid-19 vaccination. The government's efforts to promote Covid-19 vaccination are in line with the maqashid sharia concept in the form of hifz al-nafs. More than that, religion by prioritizing the safety of the soul is a manifestation of moderation.